Professionalisierung in der Studieneingangsphase der Lehrer:innenbildung Theoretische Perspektiven und empirische Befunde - Kowalski, Marlene; Leuthold-Wergin, Anca; Fabel-Lamla, Melanie; Frei, Peter; Uhlig, Bettina (Studien zur Professionsforschung und Lehrer:innenbildung, 2024)
This anthology brings together empirical and theoretical contributions on the question of the possibilities, limits and paradoxes of the professionalisation of student teachers at the beginning of their studies. Both educational science and didactic perspectives are taken into account. The contributions focus on the logic of implementation in interactions as well as on the orientations of students and various actors in teacher training and show the multifaceted and complex process of socialisation into teacher training.